The impact of the tackle: shoulder injuries in a rugby union team - Whitham, R. D. J. (British Journal of Sports Medicine, 2013)
Background: Rugby Union (rugby) is the third most popular contact sport in the world and has one of the highest reported incidences of injuries amongst all sports. Thoroughly characterising these injuries may help develop preventative methods to reduce absence from rugby at professional and amateur levels. Although the tackle event is most commonly associated with concussion and cervical nerve root injuries, shoulder injuries are responsible for up to 46% of days lost to participation at a professional level.